Measuring the Jitter of Ring Oscillators by means of Information Theory Quantifiers - Antonelli, Maximiliano (2017)
Ring oscillators (RO's) are elementary blocks widely used in digital design. Jitter is unavoidable in RO's, its presence is an undesired behavior in many applications, as clock generators. On the contrary, jitter may be used as the noise source in RO-based true-random numbers generators (TRNG). Consequently, jitter measure is a relevant issue to characterize a RO, and it is the subject of this paper. The main contribution is the use of Information Theory Quantifiers (ITQ) as measures of RO's jitter. It is shown that among several ITQ evaluated, two of them emerge as good measures because they are independent of parameters used for their statistical determination. They turned out to be robust and may be implemented experimentally. We encountered that a dual entropy plane allows a visual comparison of results.